Characterization of biodegradable food packaging films prepared with polyamide 4: Influence of molecular weight and environmental humidity. Issue 3 (2nd September 2022) - Zhang, Di; Nie, Rong; Zhang, Chunyue; Wang, Yibing; Wang, Li; Chen, Tao; Zhao, Liming
Abstract: The development of biodegradable packaging materials focuses on their barrier properties and mechanical properties, which are critical parameters for food protection. Synthetic biodegradable material polyamide 4 (PA4) may offer outstanding capacities for packaging due to its rigid molecular structure. The current study originally reveals the various physical properties of PA4 films and explores the influence of its internal structure, molecular weight, and external environment, environmental humidity, on its performance to provide further guidance for PA4 application. PA4 ( M η = 18, 000 g/mol) films showed tensile strength (TS) of 47.5 ± 1.3 MPa, elongation at break (EB) of 228% ± 30%, oxygen permeability of 7.83 ± 3.32 × 10 −17 cm 3 m −1 s −1 Pa −1, and water vapor permeability of 4.34 ± 0.06 × 10 −11 g m −1 s −1 Pa −1 . The TS and EB of PA4 improved slightly with increasing molecular weight, while the barrier characteristic remained unchanged. The moisture adsorption capabilities of PA4 films were similar to natural hydrophilic polymers. The mechanical characteristic of PA4 changed from brittle to ductile with the increase in relative humidity. Overall, PA4 can be considered to be a promising food packaging material since it presented better mechanical and oxygen barrier properties than those of commercial food packaging polymers. Abstract : Colorless and translucent polyamide 4 (PA4) films, which are both bio‐based and biodegradable, were prepared by the solution casting method in a dual‐solvent system. The physical properties of single PA4 films were originally characterized, and the effects of molecular weight and environmental humidity on PA4 were investigated.